Valproic acid-induced pancreatitis in a physically and mentally challenged child - Basak, Ratna B.; Malpani, Varsha; Kakish, Khalid; Padmanabhan, Ananthanarayan; Boeck, Andreas (Journal of Pediatric Epilepsy, 2012)
An 11-year-old child with spastic cerebral palsy, microcephaly, mental retardation and epilepsy presented with a short history of abnormal tonic posturing, irritability and poor feeding. A presumptive diagnosis of seizure relapse was made and treatment instituted along without improvement. Investigation revealed elevated laboratory markers of pancreatitis, which together with the clinical picture and evidence of pancreatic inflammation on computed tomography abdomen, led to the diagnosis of acute pancreatitis secondary to valproic acid. Symptoms of pancreatitis subsided promptly with discontinuation of valproate and supportive treatment. The clinical features of pancreatitis can easily be misinterpreted in neurologically impaired children and its diagnosis requires a high index of suspicion.
Keywords: Pancreatitis; valproic acid; epilepsy